Observing systemic conflict: The emotional affect on pastors in the Netherdutch Reformed Church of Africa - Labuschagne, Frederick J. (HTS teologiese studies, 2023)
The Netherdutch Reformed Church of Africa (NRCA) did not escape this existential crisis of conflict. It manifests in various ways resulting in the bleeding of congregations, the exodus of congregants and the closure of congregations, as many congregants that declare themselves as members of the Church do not attend worship services or participate in the Holy Communion and exit the church. The study was conducted in the NRCA to determine the effect and response formation of observed conflict by ministers in their respective congregations. The results of the study indicate that pastors and/or ministers do suffer emotional trauma because of the conflict in the congregation which, according to their own statements results in a loss of role performance. We provide an overview of the problem statement and methodology of the study. We discuss an abbreviated, theoretical perspective on conflict as a social phenomenon. We present the findings of our study and conclude with an abbreviated process to equip pastors with the necessary emotional maturity and self-management.Contribution: This study uncovers emotional trauma experienced by ministers, affecting their role performance. We offer a succinct problem statement, research methodology, and propose a scientifically informed process to enhance ministers’ emotional resilience within the NRCA.